Development of Grade 10 Students’ Mental Model on the Learning Unit of Cell Structure and Function Using Model-Based Learning - Khamkhaengkhwa, Sirinan; Dokmai, Panwilai (Ratchaphruek Journal, 2025)
This research purposed to develop Grade 10 students’ mental model on the learning unit of “Cell Structure and Function” using model-based learning approach. The target group consisted of 40 students from a very large school in Kalasin Province in the first semester of the academic year 2023. The research employed purposive sampling to select the target group. The research instruments included four lesson plans of the model-based learning on cell, cell transportation, cellular respiration, cell division and the mental model subjective test. The study utilized four operational cycles of action research, consisting of plan, action, observe and reflect and measured the students’ mental model using the mental model test at the end of each learning cycle. Data analysis statistics involved percentage, mean, and content analysis. The passing criteria of students’ mental model is the Incomplete Correct Mental Models level or higher. The result revealed that: operational cycle 1 found 65 percent of students passed the criteria of Incomplete Correct Mental Models or higher, operational cycle 2 found 75 percent of students passed the criteria, operational cycle 3 found 77.5 percent of students passed the criteria and operational cycle 4 found 100 percent of total students passed the criteria.